Agronomic Characteristics and Kinship Of 10 High Yielding Inbred Rice Varieties (Oryza Sativa L.) In West Java - Amalia, Lia; Mustofa, Sofyan; Komariah, Ai; Sondari, Nunung; Noertjahyani, Noertjahyani; Masnenah, Endeh; Turmuktini, Tien; Budiasih, R. (Ann Publisher, 2025)
Background. The success of rice production is influenced by many factors, one of which is the selection of varieties. Varieties, as a supporting factor in increasing agricultural productivity, will be able to show values according to potential yields with optimal farming management. Aims. This study aims to examine the differences in agronomic characteristics and kinship of 10 high-yielding inbred rice varieties (Oryza sativa L.) in West Java. The experiment was conducted at the Variety Display Land, Pamekaran Village, Soreang District, Bandung Regency. The experiment was conducted from April to August 2024. The experimental location was situated at an altitude of 700 m above sea level. Methods. The agronomic characteristic experiment method used a qualitative descriptive approach. In the experimental approach, a Randomized Block Design (RBD) was employed with 10 inbred rice phenotype treatments, repeated three times. The materials used in this experiment were 10 high-yielding inbred rice varieties. Result. Based on the study's results, similarities were observed in morphological characters among several inbred rice varieties, including those in Group I, Inpari 32 HDB, and Situ Bagendit, with a similarity level of 100%. In Group II, the Mekongga, Inpari 42, Inpari 33, and Inpari 30 varieties, and in Group III, the Ciherang and Padjadjaran Cakrabuana Agritan varieties, achieved a coefficient value of 78%. Conclusion. The similarity is 0.10 or 100% with a similarity coefficient level of 100% seen from the morphological character data based on the Rice UVOP Table